Preparation of Semipermeable polyvinylpyrrolidone Membranes and Study Their Chemical, Physical and Mechanical Properties - Al-Hamad, Khatoon Khalil; Al- Deri, Fawaz Ahmad; Al-Falah, Ahmad Mohamd (Journal of natural sciences, life and applied sciences, 2020)
Been we had prepared three semipermeable membranes with different concentration of polyvinylpyrrolidone by the phase inversion process. This way is a basic method to get flat membranes. the membranes were tested for chemical properties (pH rang), and physical properties (viscosity and porosity), and mechanical properties (tensile strength and strain), The results showed that polyvinylpyrrolidone (8%, 12%,15%) membrane having the higher pH range, while the polyvinylpyrrolidone (15%) membrane having the higher tensile strength and strain, but it was having the lowest porosity, viscosity was measured in low concentration was showed that polyvinylpyrrolidone (2%) solution having the higher viscosity.
Keywords: Polyvinylpyrrolidone semi-permeable film; case shift method